Adolescent Mice Are Resilient to Alcohol Withdrawal-Induced Anxiety and Changes in Indices of Glutamate Function within the Nucleus Accumbens - Lee, Kaziya M.; Coelho, Michal A.; McGregor, Hadley A.; Solton, Noah R.; Cohen, Matan; Szumlinski, Karen K. (Frontiers in Cellular Neuroscience, 2016)
Binge-drinking is the most prevalent form of alcohol abuse and while an early life history of binge-drinking is a significant risk factor for subsequent alcoholism and co-morbid affective disorders, relatively little is known regarding the biobehavioral impact of binge-drinking during the sensitive neurodevelopmental period of adolescence. In adult mice, a month-long history of binge-drinking elicits a hyper-glutamatergic state within the nucleus accumbens (Acb), coinciding with hyper-anxiety. Herein, we employed a murine model of binge-drinking to determine whether or not: 1) withdrawal-induced changes in brain and behavior differ between adult and adolescent bingers and 2) increased behavioral signs of negative affect and changes in Acb expression of glutamate-related proteins would be apparent in adult mice with less chronic binge-drinking experience (14 days, approximating the duration of mouse adolescence). Adult and adolescent male C57BL/6J mice were subjected to a 14-day binge-drinking protocol (5, 10, 20 and 40% alcohol (v/v) for 2 h/day), while age-matched controls received water. At 24 h withdrawal, half of the animals from each group were assayed for negative affect, while tissue was sampled from the shell (AcbSh) and core (AcbC) subregions of the remaining mice for immunoblotting analyses. Adult bingers exhibited hyper-anxiety when tested for defensive marble burying. Additionally, adult bingers showed increased mGlu1, mGlu5, and GluN2b expression in the AcbSh and PKCε and CAMKII in the AcbC. Compared to adults, adolescent mice exhibited higher alcohol intake and blood alcohol concentrations; however, adolescent bingers did not show increased anxiety in the marble-burying test. Furthermore, adolescent bingers also failed to exhibit the same alcohol-induced changes in mGlu and kinase protein expression seen in the adult bingers. Irrespective of age, bingers exhibited behavioral hyperactivity in the forced swim test compared to water drinkers, which was paralleled by an increase in AcbC levels of GluN2b. Thus, a 2-week period of binge-drinking is sufficient to produce a hyper-anxious state and related increases in protein indices of Acb glutamate function. In contrast, adolescents were resilient to many of the effects of early alcohol withdrawal and this attenuated sensitivity to the negative consequences of binge drinking may facilitate greater alcohol intake in adolescent drinkers.